Boy Negro (Pasig City Viva Films, 2001)
Called Negro because of his dark skin, Boy was stowaway in a ship going to Manila when he met some corrupt law enforcers who turned him into a petty thief and informer. Forced to survive on his own, willingly did all they asked him to do and grew up into a small time hood. Time came when he became expandable and faced with certain death from his former benefactors Boy Negro held a young girl hostage to call the public's attention to his plight.
DVD
Philip Salvador
Keywords: Feature films